Common carotid artery true lumen flow impairment in patients with type A aortic dissection. (3rd November 2020) - Kreibich, Maximilian; Desai, Nimesh D; Bavaria, Joseph E; Szeto, Wilson Y; Vallabhajosyula, Prashanth; Beyersdorf, Friedhelm; Czerny, Martin; Siepe, Matthias; Rylski, Bartosz; Itagaki, Ryo; Okamura, Homare; Yamaguchi, Atsushi; et al.
Abstract: OBJECTIVES: Our aim was to evaluate clinical and neurological effects of common carotid artery (CCA) true lumen flow impairment or occlusion in patients with type A aortic dissection. METHODS: Characteristics and imaging data of patients with dissected CCA secondary to acute type A aortic dissection from 3 institutions were analysed. We defined true lumen blood flow as unimpaired when the maximum true lumen diameter exceeded 50% of the complete CCA diameter, as impaired when the true lumen was compressed to ˃50% of the complete lumen, or as occluded. RESULTS: Out of 440 patients, 207 presented unimpaired CCA flow, 172 impaired CCA flow and CCA occlusion was present in 61 patients. Preoperative shock ( P = 0.045) or a neurological deficit ( P < 0.001) were least common in patients with unimpaired CCA flow and most common in those with CCA occlusion. Non-cerebral, other-organ malperfusion was common in 37% of all patients, but the incidence was similar ( P = 0.69). In patients with CCA occlusion, postoperative stroke ( P < 0.001) and in-hospital mortality (0.011) were significantly higher, while the incidences were similar between patients with unimpaired and impaired CCA flow. Mixed-effects logistic regression models showed that CCA flow impairment ( P = 0.23) or occlusion ( P = 0.55) was not predictive for in-hospital mortality, but CCA occlusion was predictive for in-hospital stroke (odds ratio 2.166, P = 0.023) CONCLUSIONS: Shock and non-cerebral, other-organ malperfusion are common in patients with CCA dissection. While there is a high risk for stroke in patients with CCA occlusion, CCA flow impairment and occlusion were not predictive for in-hospital mortality. Surgery should not be denied to patients with CCA flow impairment or occlusion. Abstract : One of the strongest risk factors to negatively affect perioperative outcomes in patients with type A aortic dissection is organ malperfusion [1].